Local Culture Materials of Indonesia in the Arabic Textbook for Senior High School in the Perspective of Cropper and Klushkorn - Muhammad Nashrullah; Kamal Yusuf (Journal of Arabic Language Studies and Teaching, 2022)
This study examines the content of local wisdom of Indonesian culture in explanatory text material in an Arabic textbook published by the Ministry of Religious Affairs in Curriculum 2013 using the theory of Kroeber and Kluchkorn in the context of sociolinguistic studies for grade XI. The approach uses a research library in this study. The collection of data was using the technique of documentation. The information from the book is classified and then analyzed through content analysis. The findings of this study indicate that the textbook contains different elements of local culture, namely, elements that are descriptive, historical, structural, and genetic. These findings can encourage students to understand philosophical values, promote character education, and provide a blend of Arabic and Indonesian culture with interesting socio-cultural information.   تهدف هذه الدراسة في محتوى الحكمة الثقافية المحلية الإندونيسية في مادة النص التوضيحي في الكتب المدرسية العربية لطلاب للصف الحادي عشر في مدرسة الثانوية التي نشرتها وزارة الدين 2013 منهج مع نظرية كروبر وكلوشكورن في إطار دراسات علم اللغة الاجتماعي. تستخدم الطريقة في هذه الدراسة البحث المكتبي. تم إجراء جمع بيانات البحث باستخدام نظرية التوثيق. يتم تصنيف البيانات من الكتاب ثم تحليلها عن طريق تحليل المحتوى. تشير نتائج هذه الدراسة إلى أن هناك عناصر متنوعة للثقافة المحلية واردة في الكتاب المدرسي، وهي العناصر الوصفية والتاريخية والبنيوية والجينية. يمكن أن تحفز هذه النتائج الطلاب على فهم القيم الفلسفية، وتعزيز تعليم الشخصية، وتوفير معلومات اجتماعية وثقافية مثيرة للاهتمام مع مزيج من الثقافة العربية والإندونيسية.